Beyond solely estrogen: Sex-based differences in platelet biology and antithrombotic response - Salma, Zaskia Nafisa; Susilo, Hendri; Wungu, Citrawati Dyah Kencono; Tandecxi, Gabriel; Nugrahani, Annisa Salsabilla Dwi (Universitas Brawijaya, 2026)
Despite increased awareness of sex differences in cardiovascular disease (CVD), disparities in sex-specific platelet biology and antithrombotic studies are still underexplored. Moreover, women are frequently underrepresented in clinical trials, with numerous research initiatives primarily focusing on estrogen while neglecting non-hormonal influences that contribute variations in thrombotic risk and treatment outcomes. We conducted a literature review to examine sex-related differences in platelet biology, such as elevated platelet counts and reactivity in females, along with distinct expression of receptors and signaling molecules. These variations influence responses to antiplatelet medications—including aspirin, P2Y12 inhibitors, and glycoprotein IIb/IIIa inhibitors, and dual antiplatelet therapy—leading to altered effectiveness and a heightened bleeding risk in women. This review emphasizes the importance of non-hormonal factors, such as transcriptomic and proteomic variations, and highlights the growing potential of omics and systems biology in identifying therapeutic targets specific to sex. Incorporating sex as a biological factor in preclinical and clinical research is crucial for enhancing risk assessment and treatment results.